Structure‐Activity Relationship and Mode‐Of‐Action Studies Highlight 1‐(4‐Biphenylylmethyl)‐1H‐imidazole‐Derived Small Molecules as Potent CYP121 Inhibitors. (22nd June 2021) - Walter, Isabell; Adam, Sebastian; Gentilini, Maria Virginia; Kany, Andreas M.; Brengel, Christian; Thomann, Andreas; Sparwasser, Tim; Köhnke, Jesko; Hartmann, Rolf W.
Abstract: CYP121 of Mycobacterium tuberculosis (Mtb) is an essential target for the development of novel potent drugs against tuberculosis (TB). Besides known antifungal azoles, further compounds of the azole class were recently identified as CYP121 inhibitors with antimycobacterial activity. Herein, we report the screening of a similarity‐oriented library based on the former hit compound, the evaluation of affinity toward CYP121, and activity against M. bovis BCG. The results enabled a comprehensive SAR study, which was extended through the synthesis of promising compounds and led to the identification of favorable features for affinity and/or activity and hit compounds with 2.7‐fold improved potency. Mode of action studies show that the hit compounds inhibit substrate conversion and highlighted CYP121 as the main antimycobacterial target of our compounds. Exemplified complex crystal structures of CYP121 with three inhibitors reveal a common binding site. Engaging in both hydrophobic interactions as well as hydrogen bonding to the sixth iron ligand, our compounds block a solvent channel leading to the active site heme. Additionally, we report the first CYP inhibitors that are able to reduce the intracellular replication of M. bovis BCG in macrophages, emphasizing their potential as future drug candidates against TB. Abstract : Similarity‐oriented library screen : Infections caused by Mycobacterium tuberculosis (Mtb) still remain among the most difficult to treat, owing to the pathogen's special characteristics within the realm of pathogenic bacteria. This report describes the development of potent inhibitors targeting an essential cytochrome P450 enzyme of Mtb, which are also able to reduce the intracellular replication of mycobacteria within macrophages.